2018
DOI: 10.1002/ps.4925
|View full text |Cite
|
Sign up to set email alerts
|

Farming system and wheat cultivar affect infestation of, and parasitism on, Cephus cinctus in the Northern Great Plains

Abstract: Cephus cinctus infestation was more common in winter wheat than in spring wheat. Organic fields with fewer cut stems also supported more parasitoids. Kamut is a genetic resource for developing C. cinctus-resistant cultivars. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…When evaluating weed communities, our results are consistent with those of Pollnac et al [33], who found that organic small grain fields in the NGP had greater weed species richness and evenness than conventional small grain fields which, in turn, could potentially support beneficial insects such as pollinators, parasitoids, and generalists predators [6,19,34,35]. However, organic farms in the drylands of NGP may face exacerbated challenges in weed management [36,37], as the weeds are often considered impediments to agricultural production [5].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When evaluating weed communities, our results are consistent with those of Pollnac et al [33], who found that organic small grain fields in the NGP had greater weed species richness and evenness than conventional small grain fields which, in turn, could potentially support beneficial insects such as pollinators, parasitoids, and generalists predators [6,19,34,35]. However, organic farms in the drylands of NGP may face exacerbated challenges in weed management [36,37], as the weeds are often considered impediments to agricultural production [5].…”
Section: Discussionsupporting
confidence: 90%
“…Kamut), a close relative of durum wheat] production (see details in [19]). Field sizes ranged from 25 ha to 70 ha and individual fields were separated by a minimum of 500 m. Organic fields had been certified by the Organic Crop Improvement Association (OCIA) International since 1989 and by the United States Department of Agriculture (USDA) organic certificate standards since 2003 [19]). All conventional fields followed a 2-year winter wheat-chemical no-till fallow rotation and all organic fields followed a multi-year continuous rotation of crops or cover crops (Table S2).…”
Section: Site Description and Cropping Historymentioning
confidence: 99%
“…Parasitism can kill up to 34% of C. cinctus larvae in a cohort and 12% of this mortality is irreplaceable, meaning that the mortality caused by B. cephi or B. lissogaster cannot be replaced by another mortality factor (Buteler et al ., ). However, the occurrence and abundance of these parasitoid species vary greatly among wheat fields and regions, compromising their effectiveness in the reliable management of this pest (Morrill et al ., ; Cárcamo et al ., ; Davis, ; Adhikari et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Bracon cephi (Gahan) and Bracon lissogaster Muesebeck (Hymenoptera: Braconidae) are important parasitoid species in wheat cropping systems. They are the only species known to attack and successfully suppress damaging populations of Cephus cinctus Norton (Hymenoptera: Cephidae), which is the most destructive pest of wheat in the Northern Great Plains of North America (Morrill et al ., ; Runyon et al ., ; Weaver et al ., , ; Beres et al ., ; Peterson et al ., ; Rand et al ., ; Cárcamo et al ., ; Buteler et al ., ; Adhikari et al ., ; Bekkerman & Weaver, ). Parasitism can kill up to 34% of C. cinctus larvae in a cohort and 12% of this mortality is irreplaceable, meaning that the mortality caused by B. cephi or B. lissogaster cannot be replaced by another mortality factor (Buteler et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The wheat stem sawfly, Cephus cinctus Norton, is a major pest of wheat in western North America with a southward expanding geographic range likely driven by localized adaptation to cultivated crops from surrounding wildlands (Beres et al 2011;Lesieur et al 2016;Adhikari et al 2018;Varella et al 2018). It is a native species that also uses many other grass hosts and hence plays an important role in the ecology of grasslands (Cockrell et al 2017).…”
Section: Introductionmentioning
confidence: 99%